PELATIHAN MENGHAFAL AYAT ALKITAB MELALUI LAGU BAGI MAHASISWA SEKOLAH TINGGI TEOLOGI INJILI ARASTAMAR (SETIA) JAKARTA - Putra Wijalin Halawa (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
This article aims to apply to learning the Bible/The Word of God by using methods through songs to make the students quickly memorise verses they like in the Bible. The goal of The word of God is to fulfil and direct our way through God. (2 Timothy 3:15-17). The Bible told us that the songs had authority and significantly impacted Christianity'sChristianity's lives. The music chord will impact a hearer'shearer's soul. The method used is training students to memorise the Bible through songs by involving them in choosing the verses they like, and then they will sing those verses to help them quickly memorise verses. After that, the students will be invited to repeat that verses until they truly memorise verses. Bible songs are helping the students to upgrade their brains to memorise the verses of the Bible. Through this method, the students desire to know the Bible more and more.